Fueling young athletes - Mangieri, Heather R. 1974- (Human Kinetics, 2017)
"Fueling Young Athletes stresses the importance of balanced daily nutrition as part of an overall eating plan for health, growth, development, and sport performance and shows how to implement that plan"--Publisher's description.